Answer:
Simplifying
12x + 3 = 11x + 9
Reorder the terms:
3 + 12x = 11x + 9
Reorder the terms:
3 + 12x = 9 + 11x
Solving
3 + 12x = 9 + 11x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-11x' to each side of the equation.
3 + 12x + -11x = 9 + 11x + -11x
Combine like terms: 12x + -11x = 1x
3 + 1x = 9 + 11x + -11x
Combine like terms: 11x + -11x = 0
3 + 1x = 9 + 0
3 + 1x = 9
Add '-3' to each side of the equation.
3 + -3 + 1x = 9 + -3
Combine like terms: 3 + -3 = 0
0 + 1x = 9 + -3
1x = 9 + -3
Combine like terms: 9 + -3 = 6
1x = 6
Divide each side by '1'.
x = 6
Simplifying
x = 6